2019
DOI: 10.1039/c9nr01213c
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected benefits of stacking faults on the electronic structure and optical emission in wurtzite GaAs/GaInP core/shell nanowires

Abstract: Superior passivation of GaInP shell and the revealed carrier dynamics in WZ polytype GaAs nanowires.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…The carrier mobility and photoresponsivity could be further enhanced by addition of an Al 2 O 3 or HfO 2 passivation layer that can suppress the negative influence of surface defect states and atmospheric molecules [11]. Yuan et al showed that nanowire photodetector responsivity can also be enhanced using in situ passivation by epitaxial growth of a GaInP shell on GaAs core nanowires [75], whereas Li et al demonstrated enhanced infrared photoresponse of GaAsSb nanowires by the in situ passivation of adding an InP shell [76]. Moreover, core-shell heterostructures, such as InAs/AlSb core-shell [46], form a type-II bandgap alignment that further improves charge carrier separation, photosensivity, and photoresponse.…”
Section: Photoconductorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The carrier mobility and photoresponsivity could be further enhanced by addition of an Al 2 O 3 or HfO 2 passivation layer that can suppress the negative influence of surface defect states and atmospheric molecules [11]. Yuan et al showed that nanowire photodetector responsivity can also be enhanced using in situ passivation by epitaxial growth of a GaInP shell on GaAs core nanowires [75], whereas Li et al demonstrated enhanced infrared photoresponse of GaAsSb nanowires by the in situ passivation of adding an InP shell [76]. Moreover, core-shell heterostructures, such as InAs/AlSb core-shell [46], form a type-II bandgap alignment that further improves charge carrier separation, photosensivity, and photoresponse.…”
Section: Photoconductorsmentioning
confidence: 99%
“…Due to the morphology and associated properties of the nanowires, the performance of these photodetectors could be tuned by adjusting the Schottky barrier height, which is sensitive to the carrier generation and transport [88]. As the photocurrent is normally localized near the metal electrode-nanowire contact, scanning photocurrent mapping can be an effective way to investigate the effects of Schottky barriers on the mechanisms of photoconduction [32,75,89]. Compared to the M-S structure-based Schottky barrier photodiode that can produce photocurrent at zero bias with a gain no more than 1 but very fast response time [32], the M-S-M structure is symmetrical at zero bias with a built-in potential well for photoexcited carriers until a high external voltage is applied to break through the potential barrier.…”
Section: Junction Based Photodetectorsmentioning
confidence: 99%
“…[ 55 ] Recombination can occur between electrons and holes trapped in neighboring ZB/WZ segments of a NW, termed as type II recombination. [ 56,57 ] The lower recombination rates of the spatially separated charge carriers lead to a fast decrease in PL intensity at early times due to the trapping of free carriers, but also to a slower (i.e., nonexponential) subsequent decay of the PL signal, as observed in the measured TRPL decays.…”
Section: Resultsmentioning
confidence: 85%
“…[42] WZ/ZB homojunction has been intensively investigated in III-V nanowires, in which they exhibit type-II band alignment and have a great significance in different applications. [45][46][47][48] Here, we expand the WZ/ZB homojunction structure from 1D nanowires to 2D nanomembranes, which can potentially provide additional functionality such as separation of charge carriers to the respective nanomembrane layer for high speed devices.…”
Section: Resultsmentioning
confidence: 99%